Fiscal Policies and Gender Equality. (Washington, D.C. : International Monetary Fund, 2018)
This volume contains seven chapters that consider how fiscal policies can address women's and girls' disadvantages in education, health, employment, and financial well-being. Researchers from a joint collaboration between the International Monetary Fund and the UK's Department for International Development presented papers at a 2016 international conference on gender budgeting at the International Monetary Fund headquarters in Washington, DC, and detail the findings of their work here, which draws on published materials, a questionnaire sent to ministries of finance to all International Monetary Fund member countries, and interviews with country officials and international organizations that offer technical assistance to countries seeking to implement gender budgeting. They describe key gender budgeting efforts planning, allocating, and monitoring government expenditures and taxes to address gender inequality in sub-Saharan Africa, Asia and the Pacific, Europe, Latin America and Canada, the Middle East and Central Asia, and the Pacific Islands and Caribbean.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet